Environmental, Social and Governance Practices and Corporate Financial Performance: Evidence from Johannesburg Stock Exchange Listed Firms - Bendeman, Justin; Khumalo, Sibanisezwe; Phakathi, Sandile (International Journal of Economics and Financial Issues, 2026)
This study investigates the relationship between Environmental, Social, and Governance (ESG) practices and corporate financial performance (CFP) among firms listed on the Johannesburg Stock Exchange (JSE) from 2007 to 2021. Using difference-in-difference (DiD), fully modified ordinary least squares (FMOLS), and quantile regression approaches, the analysis evaluates both accounting-based and market-based performance indicators, including return on assets, return on equity, Tobin’s Q, and share returns. Results reveal a negative association between ESG scores and accounting measures of profitability but a positive link with market valuation and share returns. High-ESG “leader” firms outperform their peers, suggesting that financial benefits accrue primarily to firms that engage deeply in sustainability practices. Sectoral analysis highlights that secondary-sector firms experience stronger ESG-related gains compared to primary-sector firms. The findings contribute to the emerging-market literature by providing robust empirical evidence from South Africa and offer insights for policymakers, investors, and corporate managers seeking to align sustainability with financial performance.